2019
DOI: 10.4274/tjod.galenos.2018.21298
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Ankaferd Blood Stopper<sup>®</sup> in an experimental Asherman syndrome model created in rats

Abstract: Objective: Asherman syndrome (AS) is a progressive disease involving menstrual disorders, recurrent pregnancy losses, and infertility developing as a result of partial or full blockade of the uterine cavity with adhesions. AS generally develops after trauma to the basal layer of the endometrium. In spite of a variety of methods such as adhesiolysis, inserting intrauterine devices, and administering high doses of estrogen, treatments remain insufficient. This study aimed to assess the effects of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Moreover, Dynactin, EGR-1, Midkine, NF-1, Twinfilin, V-Myc, and YY1 (Yin Yang 1) can contribute both the anti-inflammatory and tissue-healing effects of ABS with various mechanisms [46] . Studies also highlight the potential benefits of ABS in numerous distinct inflammatory conditions related to the oral mucosa, intestinal mucosa, cartilage tissue, liver, pericardium, cervix and uterus [19] , [47] , [48] , [49] , [50] , [51] .…”
Section: Evaluation and Discussion Of The Hypothesismentioning
confidence: 99%
“…Moreover, Dynactin, EGR-1, Midkine, NF-1, Twinfilin, V-Myc, and YY1 (Yin Yang 1) can contribute both the anti-inflammatory and tissue-healing effects of ABS with various mechanisms [46] . Studies also highlight the potential benefits of ABS in numerous distinct inflammatory conditions related to the oral mucosa, intestinal mucosa, cartilage tissue, liver, pericardium, cervix and uterus [19] , [47] , [48] , [49] , [50] , [51] .…”
Section: Evaluation and Discussion Of The Hypothesismentioning
confidence: 99%
“…In another study, intravaginal ABS injection caused a significant decrease in the number of inflammatory cells in the cervical mucosa and ABS had significant protective effects on cervical erosion [33]. In another animal study, it was observed that ABS administration improved uterine fibrosis and histopathological inflammation by lowering the level of inflammatory markers such as IL-1 and IL-6 [67].…”
Section: The Usage Of Abs In Wound Healingmentioning
confidence: 99%